Limits and Restrictions on the Exercise of Civil Rights - Sloma, Valentyna; Moscaliuk, Nadiia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
An important place among the issues that arise in the exercise of subjective civil rights is taken by the question of the limits and restrictions on their exercise. In exercising his subjective right, a participant in a civil legal relationship is always in interaction with other persons, he cannot act indefinitely without taking into account the interests of these persons. According to Art. 13 of the Civil Code of Ukraine, a person exercises civil rights within the limits provided by the contract or acts of civil legislation. In exercising his rights, a person is obliged to refrain from actions that could violate the rights of others, harm the environment or cultural heritage. Actions of a person committed with intent to harm another person, as well as abuse of rights in other forms are not allowed.The article analyzes doctrinal approaches to understanding the limits and limitations of civil rights. Attention is paid to the interpretation of these categories, their content and classification.It is emphasized that the limits of the exercise of civil rights are a kind of guarantee of proper protection of the rights and legitimate interests of participants in civil relations. It is the limits of the exercise of subjective rights that characterize the process of exercising their powers without violating the rights and legitimate interests of other participants, which indicates the effectiveness of the limits of civil rights, defined by law or contract.In some cases, restrictions may be imposed on the exercise of certain powers by participants in civil relations in order to enable another party to exercise its powers. In particular, this applies to the procedure for selling a share in the right of joint partial ownership (Article 362 of the Civil Code of Ukraine), the peculiarities of the regulation of servitude relations (Article 403 of the Civil Code of Ukraine), etc.It has been concluded that the limits of the exercise of civil rights determine certain regulatory frameworks for the exercise of subjective rights, and the limitations of subjective rights are to narrow the powers of the participant in civil relations. Limits are set for all participants of the legal relations, and restrictions are inherent in the exercise of certain subjective rights.